Wagner's law is still applicable - Dolenc, Primož (Naše gospodarstvo, 2009)
This paper tests the validity of Wagner''s law for Slovenia and the hypothesis that the government elected in 2004, despite its claims, has not significantly changed the trends in public finances. We test six empirical versions of Wagner''s law for the period 1992 to 2007. Data undoubtedly confirm five of six versions of Wagner''s law; therefore, we conclude that Wagner''s law also holds for Slovenia. The analysis also shows that the new political orientation in Slovenia could or would not significantly change the trends in public finances.
Keywords: ekonomske teorije; javne finance; public finance; public sector; javni sektor; Slovenia; Slovenija